A case report of granulomatosis with polyangiitis (GPA) - A rare presentation of strawberry gingiva to dentists and oral and maxillofacial surgeons - Dr Jvalant Nayan Parekh; Dr Nagamuttu Ravindranathan (Elsevier, 2021)
We present a case of isolated strawberry gingivitis without systemic involvement in an otherwise healthy young male.Early recognition and biopsy allowed for successful management of the lesion and initiation of systemic therapy for the Granulomatosis with polyangiitis (GPA), with no recognised end-organ damage.The key learning points include having a low threshold for biopsy and early referral to an oral and maxillofacial surgeon with a view to prompt assessment and commencement of treatment with planned long term follow up.